Resting heart rate variability in professors: Impact of psychological stress, obesity and blood pressure - Nacha Samadi Andrade Rosario; Perciliany Martins de Souza; Poliana Elisa Assunção; Fernando Luiz Pereira de Oliveira; Eduardo Bearzoti; Kelerson Mauro de Castro Pinto; Gabriela Guerra Leal Souza (Kazimierz Wielki University, 2021)
Objective: University professors are prone to show physical and psychological diseases related to excessive workload. Such overwork can affect the functioning of the autonomic nervous system, leading to a decrease in heart rate variability (HRV). HRV reflects the continuous fluctuation of the R-R intervals due to sympathetic and parasympathetic actions in the heart and is associated with good physical and psychological health. We aimed to evaluate whether psychological stress and anthropometric and clinical variables influence HRV at rest in professors. Methods: University professors of both sexes (N=65; 41 men) participated. We collected Anthropometry and Clinical variables, Psychological stress, and HRV parasympathetic parameters (square root mean squares of the differences between RR intervals: RMSSD, number of successive differences between RR intervals, which are > 50 ms: NN50 and high frequency - HF). Results:  Four principal components (PCs) represented 68.29% of the data total variation. Principal component 1 (PC1) was called the good cardiac regulation component. PC2 was called the component of reduced stress symptoms. PC3 was named favorable working conditions component. PC4 was denominated component of labor and physiological deregulation. Each HRV parameter was associated with each PC through the use of regression models. The RMSSD was positively associated with PC2. The NN50 was positively associated with PC2 and PC3. HF was positively associated with PC3 and PC4. Conclusions: HRV parasympathetic parameters, which represent good physical and mental health, are positively associated with the components of reduced stress symptoms, favorable working conditions, and labor and physiological deregulation. Objetivo: Professores universitários são propensos a apresentar doenças físicas e psicológicas relacionadas à carga horária excessiva. Esse excesso de trabalho pode afetar o funcionamento do sistema nervoso autônomo, levando a uma diminuição da variabilidade da frequência cardíaca (VFC). A VFC reflete a flutuação contínua dos intervalos RR devido às ações simpáticas e parassimpáticas no coração e está associada a uma boa saúde física e psicológica. Objetivamos avaliar se o estresse psicológico e as variáveis antropométricas e clínicas influenciam a VFC em repouso em professores. Métodos:Participaram professores universitários de ambos os sexos (N = 65; 41 homens). Coletamos variáveis antropométricas e clínicas, estresse psicológico e parâmetros parassimpáticos da VFC (raiz quadrada da média dos quadrados das diferenças entre os intervalos RR: RMSSD, número de diferenças sucessivas entre os intervalos RR, que são> 50 ms: NN50 e alta frequência - HF). Resultados:  Quatro componentes principais (PCs) representaram 68,29% da variação total dos dados. O componente principal 1 (PC1) foi denominado componente de boa regulação cardíaca. PC2 foi chamado de componente de redução dos sintomas de estresse. O PC3 foi denominado componente de condições favoráveis de trabalho. PC4 foi denominado componente do parto e desregulamentação fisiológica. Cada parâmetro de VFC foi associado a cada PC por meio do uso de modelos de regressão. O RMSSD foi positivamente associado ao PC2. O NN50 foi associado positivamente com PC2 e PC3. HF associou-se positivamente com PC3 e PC4. Conclusões: Os parâmetros parassimpáticos da VFC, que representam boa saúde física e mental, estão positivamente associados aos componentes de redução dos sintomas de estresse, condições favoráveis de trabalho e desregulamentação fisiológica e laboral.